Relevate - Cannizzaro, Anthony R.; Hallaq, Tom G. (Kansas State University, 2018)
I wanted to reach out about the work I've been doing with Relevate, which is a mobile hub for trustworthy and relevant romantic relationship resources. We are a multidisciplinary team of researchers who are on a mission to make research-based information about romantic relationships accessible to all. We would like media products that target our collaborators (other researchers) to get them to want to share their research and engage with the Relevate website and app. In doing so we would also want some content that talked about the value of Relevate for end users, too.
Keywords: Natalie Pennington